Free trade: why, when and for whom? - D. NAYYAR (PSL Quarterly Review, 2013)
The free-trade argument as situated in the normative dimension of orthodox theory had an explicit prescriptive role of expressing that free trade is efficient. Moreover, the factor-price equalisation theorem as framed in the positive dimension of orthodox theory served an implicit prescriptive role stating that free trade is also equitable. As evidenced by the influence of political realities the developments in the international trading system, there has been variation in the application of the free trade doctrine across time. The evolution of economic thinking about free trade is examined. Amongst the important issues explored are the reasons for departure from free trade. The reality of the present pattern of free trade is considered in the light of the Uruguay Round agreement.